Information Communication Technology for enhanced credit Facilitation decisions for Agricultural Cooperatives in Uganda - Ahabyoona, Faith; Lubega, Jude T.; Kibukamusoke, Martha (International Journal of Technology and Management, 2019)
This paper unveils that problem grounded Information Communication Technology based solutions (ICTs) can enhance credit facilitation decision making that can ultimately improve financial Performance in Agricultural Cooperatives. This paper is motivated by two issues. Firstly, that the current financial performance measured in terms of loan portfolio, liquidity ratio and non-repayable loans is a result of decisions made in credit facilitation by cooperative managers in Uganda. Secondly that Information Communication Technology can provide an innovative mechanism which is theoretically grounded, and can improve the way of working of credit facilitation in agricultural cooperatives. This innovative ICT mechanism is called a Decision Enhancement Credit Facilitation Approach (DECFA) which is capable of enhancing the decisions of the credit facilitation process. The design of the DECFA was two- folded that is translating credit facilitation decision challenges into credit facilitation decision requirements. The requirements were translated into case scenarios which were presented as user case diagrams. These user case diagrams were translated into suites that were implemented in a studio environment. The design of the user case diagrams was done using the Unified Modified Language (UML). A fully designed DECFA can enhance credit facilitation decisions in agricultural cooperatives and it’s supported by information communication technology.
Keywords: Credit facilitation decisions; Agricultural cooperatives; Financial Performance; ICT